2004
DOI: 10.1144/gsl.sp.2004.238.01.16
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic flow paths and palaeomagnetism of the Miocene Stoddard Mountain laccolith, Iron Axis region, Southwestern Utah, USA

Abstract: The Stoddard Mountain laccolith is part of a complex of Early Miocene laccoliths intruded along the western edge of the Colorado Plateau in the Iron Axis region of Southwestern Utah. Most Colorado Plateau laccoliths (e.g. Henry and La Sal Mountains) are considered to be fed by a central axial feeder system. However, detailed mapping in the Iron Axis region suggests that the Stoddard Mountain laccolith was fed laterally from the west. Structural and field data suggest the quartz monzonitic magma initially migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…These findings are consistent with those of several other studies on granitoids of similar grain size (e.g. Ferré et al 1999;Petronis et al 2004;Martins et al 2011).…”
Section: Characterization Of Magnetic Mineralogy and Significance Of Amssupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with those of several other studies on granitoids of similar grain size (e.g. Ferré et al 1999;Petronis et al 2004;Martins et al 2011).…”
Section: Characterization Of Magnetic Mineralogy and Significance Of Amssupporting
confidence: 93%
“…9b). Lateral emplacement of magma initially occurred as a thin sheet that extended to the full diameter of the intrusion to form a disc shape prior to vertical inflation (Pollard & Johnson 1973;Corry 1988;Petronis et al 2004). Early emplacement was driven by excess magma pressure and was facilitated by ductile up-doming of the bounding roof that accommodated pluton inflation (Fig.…”
Section: Mechanism Of Emplacementmentioning
confidence: 99%
“…The fabric pattern that Stevenson et al (2007b) revealed did not provide any evidence of vertical magma flow consistent with a ring-dyke style feeder. Instead, AMS data revealed lateral magma flow directed NNE indicated by northward divergence of the AMS lineation pattern (see Petronis et al 2004). Stevenson et al (2007b) acknowledged, however, that the inflow may have alternatively been from the eastern (or northeastern) margin, possibly from an unexposed ring-dyke style feeder, or from subjacent dykes.…”
Section: Laccoliths As Opposed To Cauldron Subsidencementioning
confidence: 99%
“…Moreover, to a certain extent, it provides an estimate of the amount of strain (Borradaile and Henry 1997;Bouchez 1997Bouchez , 2000. Even in weakly anisotropic material, it is now widely accepted that the magnetic lineations and foliations potentially reflect the magmatic fabric and can provide information on magma migration, flow geometries, and regional strain (King 1966;Owens and Bamford 1976;Hrouda 1982;Rochette 1987;Rochette et al 1992;Tarling and Hrouda 1993;Bouchez 1997;Borradaile and Henry 1997;Dietl 1999;Sant'Ovaia et al 2000;Petronis et al 2004Petronis et al , 2009Petronis et al , 2013Horsman et al 2005;Sidman et al 2005;Žák et al 2005O'Driscoll et al 2006;Stevenson et al 2007;Kratinová et al 2010). In the following, we consider the possible driving mechanisms that formed the fabrics revealed by AMS data from the Trosky volcano.…”
Section: Ams-inferred Magma Flow Directionsmentioning
confidence: 99%